Rezolvati ecuatia.:(x+1)²+2(x-2)(x+2)=(3x-1)(x-3)+2
Răspunsuri la întrebare
Răspuns de
12
x²+2x+1+2(x²-2²)=3x²-9x-x+3+2⇔
⇔x²+3x²+2x+9x+x+2x²=-1-2+8+3+2⇔
⇔6x²+12x=10⇔
⇔6x(x-2)=10
ATAT RAMANE
⇔x²+3x²+2x+9x+x+2x²=-1-2+8+3+2⇔
⇔6x²+12x=10⇔
⇔6x(x-2)=10
ATAT RAMANE
florin12345:
trebuie sa dea 1
Răspuns de
31
x²+2x+1²+2(x²+2x-2x-4)=3x²-9x-x+3+2
x²+2x+1+2x²+4x-4x-8=3x²-10x+5
3x²+2x-7=3x²-10x+5
3x²-3x²+2x+10x=5+7
12x=12
x=12/12
x=1
x²+2x+1+2x²+4x-4x-8=3x²-10x+5
3x²+2x-7=3x²-10x+5
3x²-3x²+2x+10x=5+7
12x=12
x=12/12
x=1
Alte întrebări interesante
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Matematică,
10 ani în urmă